Therapeutic effect of chidamide on relapsed refractory angioimmunoblastic T-cell lymphoma: A case report and literature review. Issue 2 (January 2018) - Jin, Jingxia; Zheng, Cuiping; Wu, Shenghao
Abstract: Introduction: Angioimmunoblastic T-cell lymphoma (AITL) is a kind of rare peripheral T cell lymphoma, which usually has acute onset at old age. Materials and methods: Here we report a case of relapsed refractory AITL, which has achieved obvious curative effect after treatment with chidamide. Results: Initially, the patient received 7 courses of treatment with recombinant human endostatin (endostar)+CHOP. The patient achieved complete remission, but suffered from recurrence later. After changing chemotherapy regimens, the outcome was still not satisfactory, and the patient developed systemic skin infiltration and rashes. After 2 courses of chemotherapy with chidamide (30 mg) twice a week + intravenous injections with cyclophosphamide (0.1 g) twice every other day + thalidomide (50 mg) every night, the patient began with the oral intake of chidamide, and the therapeutic effect was satisfactory, with diminishing systemic rashes and shrunken lymph nodes. Discussion and conclusions: Chidamide has good therapeutic effect in the treatment of AITL, which provides a novel therapeutic strategy for relapsed refractory AITL. However, more cases are still needed to further validate its efficacy.